Kinetic Resolution of sec‐Thiols by Enantioselective Oxidation with Rationally Engineered 5‐(Hydroxymethyl)furfural Oxidase. (15th February 2018) - Pickl, Mathias; Swoboda, Alexander; Romero, Elvira; Winkler, Christoph K.; Binda, Claudia; Mattevi, Andrea; Faber, Kurt; Fraaije, Marco W.
Abstract: Various flavoprotein oxidases were recently shown to oxidize primary thiols. Herein, this reactivity is extended to sec ‐thiols by using structure‐guided engineering of 5‐(hydroxymethyl)furfural oxidase (HMFO). The variants obtained were employed for the oxidative kinetic resolution of racemic sec ‐thiols, thus yielding the corresponding thioketones and nonreacted R ‐configured thiols with excellent enantioselectivities ( E ≥200). The engineering strategy applied went beyond the classic approach of replacing bulky amino acid residues with smaller ones, as the active site was additionally enlarged by a newly introduced Thr residue. This residue established a hydrogen‐bonding interaction with the substrates, as verified in the crystal structure of the variant. These strategies unlocked HMFO variants for the enantioselective oxidation of a range of sec ‐thiols.